2022
DOI: 10.1371/journal.pone.0269281
|View full text |Cite
|
Sign up to set email alerts
|

High-affinity anti-Arc nanobodies provide tools for structural and functional studies

Abstract: Activity-regulated cytoskeleton-associated protein (Arc) is a multidomain protein of retroviral origin with a vital role in the regulation of synaptic plasticity and memory formation in mammals. However, the mechanistic and structural basis of Arc function is poorly understood. Arc has an N-terminal domain (NTD) involved in membrane binding and a C-terminal domain (CTD) that binds postsynaptic protein ligands. In addition, the NTD and CTD both function in Arc oligomerisation, including assembly of retrovirus-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 91 publications
0
41
0
Order By: Relevance
“…Tools that would allow labeling or functional manipulation of endogenous Arc would be an advantage. To this end, single‐domain antibodies (nanobodies) that bind the Arc CA domain have been developed 138,139 . The recombinant nanobodies bind with high affinity (low nM Kd) and are suitable for expression in mammalian cells as intra‐bodies.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tools that would allow labeling or functional manipulation of endogenous Arc would be an advantage. To this end, single‐domain antibodies (nanobodies) that bind the Arc CA domain have been developed 138,139 . The recombinant nanobodies bind with high affinity (low nM Kd) and are suitable for expression in mammalian cells as intra‐bodies.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…To this end, single‐domain antibodies (nanobodies) that bind the Arc CA domain have been developed. 138 , 139 The recombinant nanobodies bind with high affinity (low nM Kd) and are suitable for expression in mammalian cells as intra‐bodies. One of the nanobodies, ArcNb H11, binds selectively to the N‐lobe ligand pocket with 35 000 times higher affinity than stargazin, competitively inhibits stargazin binding, and allows affinity purification of intra‐cellular Arc.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…The high-resolution structure of full-length Arc (flArc) remains unknown, as the molecular flexibility of Arc hinders its crystallization [36]. To face this problem, anti-Arc nanobodies have been developed and used as crystallization chaperones for the rat and human Arc C-terminal domain (Arc-CTD) [37]. Isothermal titration calorimetry (ITC) revealed that the anti-Arc nanobody H11 can displace a TARPγ2-derived peptide from the multi-peptide binding pocket of flArc, suggesting a role for this nanobody as a functional modulator of Arc function [37].…”
Section: Introductionmentioning
confidence: 99%
“…To face this problem, anti-Arc nanobodies have been developed and used as crystallization chaperones for the rat and human Arc C-terminal domain (Arc-CTD) [37]. Isothermal titration calorimetry (ITC) revealed that the anti-Arc nanobody H11 can displace a TARPγ2-derived peptide from the multi-peptide binding pocket of flArc, suggesting a role for this nanobody as a functional modulator of Arc function [37]. This finding has prompted an increased interest in anti-Arc nanobodies that selectively bind Arc-NL, as it mediates several essential functions for the regulation of synaptic plasticity, and as the binding event could affect full-length Arc conformation and oligomeric state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation